THE USE OF FLOATING CUBE-SHAPED ?-CARRAGEENAN AS CD(II) ION ADSORBENT - Rifky Syahida, Silfa
Currently, water pollution by heavy metals is a serious environmental issue that requires more attention from various communities. An example of a heavy metal commonly found in aquatic ecosystems is cadmium. Cadmium is a heavy metal that is toxic and causes liver and kidney disorders. This research aims to develop a cadmium heavy metal separation method to overcome water pollution problems. The method developed in this research is the adsorption method. The adsorbent used is ?-carrageenan. Carrageenan is a polymer obtained from seaweed and has a strong adsorption ability to heavy metals due to the presence of hydroxyl and sulfate groups in its chemical structure. The adsorbent preparation in this study was carried out by mixing the ?-carrageenan powder with KCl. The composition between ?-carrageenan and KCl that produce adsorbents with the best resistance in water is 2.5% ?-carrageenan with the addition of 0.05 M KCl. In this study, the ?-carrageenan adsorbent used has a cube shape and has the ability to float in liquid media. The ability to float makes the separation process between adsorbent and adsorbate easier to do. The drying technique used in making this adsorbent is freeze-dried so that a hollow adsorbent is formed. The ?-carrageenan cube adsorbent was then characterized using Fourier Transform Infrared Spectroscopy (FTIR) and Scanning Electron Microscopy (SEM). FTIR results of ?-carrageenan cube adsorbent after contact with cadmium solution showed a shift in the absorption peaks of O-H and S=O functional groups while SEM results showed that the adsorbent surface became rougher after contact. Adsorbent cubes ?-carrageenan cube adsorbent can float for up to 2 hours with a swelling degree of 6285.98%. From the results, the adsorption of Cd(II) ions using ?-carrageenan cube adsorbent reached optimum condition at pH 5, adsorbent mass 0.15 gram, and contact time 1 hour. The adsorption of Cd(II) ions using ?-carrageenan adsorbent followed the pseudo-second-order kinetics model and Langmuir isotherm model with Qmax of 67.87 mg.g?1. Based on the thermodynamics, the adsorption process was exothermic and spontaneous as indicated by the ?G values at 303, 308, and 313 K respectively of ?53.24, ?53.44, and ?53.65 kJ.mol–1 as well as ?H and ?S values of ?40.81 kJ.mol–1 and 41.02 J.mol?1.K–1. The ?-carrageenan cube adsorbent was able to survive until the 4th cycle.